Basque cinema a cultural and political history - Stone, Rob; Rodríguez, María Pilar 1964- (Tauris world cinema series, 2015)
This book is the definitive study of Basque cinema, revealing how film has always been a vital medium for articulating the Basque region's unique identity and politics.